Scale back or forge ahead? Opportunities and risks associated with the Intergovernmental Conference on the European Constitution - Andreas Maurer (Stiftung Wissenschaft und Politik (SWP), 2003)
On 4 October 2003 the heads of state and government and foreign ministers of all 25 existing and imminently acceding Member States of the European Union, European Commission President Romano Prodi and two representatives of the European Parliament opened the Intergovernmental Conference (IGC) convened in Rome to discuss the draft European Constitution. Just under nine weeks from that date, by mid-December, after a probable total of nine meetings, the Constitution will supposedly be adopted. (SWP Comments / SWP)
Keywords: 320